Does pubescence increase uptake of nutrient deposition on leaves? - Mendel, Lilyane I J (Department of Biological Sciences, 2017)
1. Leaf hairs have been associated with reducing environmental stress by increasing reflectance and the thickness of the boundary layer, however, such effects are more obvious in species with dense trichome layers. The adaptive functions for species with sparse leaf hair cover, such as in the Cape Proteaceae species of the Cape Floristic Region (CFR), remain unknown. 2. We postulated that leaf hairs of the Proteaceae in the CFR facilitate both nutrient absorption and water retention on the leaf surface. Leaf hair distribution is expected to show a pattern relative to the higher levels of atmospheric nutrients with proximity to the coast. 3. We followed a three pronged approach, this involved (i) evaluating the relationship of leaf pubescence with leaf surface water holding capacity, water uptake and nitrogen absorption from wet deposition for 12 Proteaceae species from the CFR, under controlled conditions; (ii) evaluating the relationship between leaf pubescence and plant height of 39 Proteaceae species from the CFR and (iii) comparing visual scores of pubescence with the relative proximity of the plants to the coast (oceanic index/continentality) of 205 Proteaceae species. 4. There was a positive correlation between leaf pubescence (0 to 8 x 10⁶ m⁻²) and water holding capacity for the 12 experimental Proteaceae species, however, water uptake did not vary with hairiness. ¹⁵NO₃⁻, ¹⁵NH₄⁺ and ¹⁵N-glycine solutions were each independently applied as wet deposition to the 12 experimental Proteaceae species. The uptake of glycine showed a positive correlation with hairiness overall and for Protea, whereas nitrate and ammonium uptake were positively correlated only with hairiness of Leucospermum. 5. Average plant height was positively correlated with leaf hair density of the 39 Proteaceae species. The visual score of pubescence was significantly different for each genus and there was no correlation between leaf pubescence and distance from the coast for the 205 field Proteaceae species. 6. Leaf hairs probably play a role in reducing environmental stresses, however, it is also possible that they play a role in water retention and nutrient absorption. Hairs on leaves vary in arrangement and morphological characteristics, thus they accordingly, probably serve different functions.